CORRELATION BETWEEN FINANCIAL LITERACY VARIABLES AND HOUSEHOLD SAVINGS BEHAVIOUR IN TWO SELECTED MUNICIPALITIES IN SOUTH AFRICA - Mbukanma, Ifeanyi; Rena, Ravinder (International Journal of Psychosocial Rehabilitation, 2021)
This study was conducted to ascertain financial literacy variables that have a statisticallysignificant impact on household savings behaviour. Thus, to achieve this objective, financialliteracy micro-variables were used to obtain quantitative data from the employees of the Cityof Tshwane and Mahikeng Municipality in South Africa. Correlation statistical analysis andfactor analysis were performed to identify financial literacy micro-variables that have asignificant impact on household savings behaviour as well as a confirmatory factor analysisthrough structural equation modelling. Hence, the findings of this study reveal that financialliteracy variables under the domain of financial control, planning and knowledge have apositive correlation with determinant variables of South African household savings behaviourand recommend that stakeholders in charge of financial literacy and savings campaigns inSouth Africa should adopt the study's contribution which identifies financial and savingsliteracy as core variables that can improve savings behaviour of South African households